SISTEM PENGAMANAN DOKUMEN MENGGUNAKAN ALGORITMA KRIPTOGRAFI ADVANCED ENCRYPTION STANDARD (AES-256) - Ridho, Akbar; Romli, Moh Ali (Jurnal Informatika Teknologi dan Sains (Jinteks), 2024)
The implementation of document security systems using the Advanced Encryption Standard (AES-256) algorithm has become a crucial solution in addressing the challenges of information security in the digital era. The increasing vulnerability of sensitive data to hacking and information theft has created an urgent need for more effective security strategies. The primary issues identified include the high risk of unauthorized access to critical information, limitations of existing security methods, and the need for encryption that ensures both the confidentiality and integrity of data. This research employs a methodology that encompasses literature review, problem identification, system design, implementation, and black box testing. The designed system allows users to encrypt and decrypt documents through a web-based platform, focusing on ease of use and security. The test results demonstrate that AES-256 is effective in protecting sensitive data from unauthorized access. The conclusion of this study emphasizes the importance of integrating encryption algorithms with other security technologies to further enhance data protection, as well as recommendations for future research to improve usability for non-technical users